Numerical study on the effects of blood perfusion and tumor metabolism on tumor temperature for targeted hyperthermia considering a realistic geometrical model of head layers using the finite element method - Kazemi Alamouti, Adeleh; Habibi, Mohammad Reza; Mazidi Sharfabadi, Mohammad; Akbari Lalimi, Hossein (SN applied sciences, 2021)
The main aim of the present work is to determine the temperature distribution in the normal and cancerous tissues to achieve the desired condition of hyperthermia. Hyperthermia can be defined as the mild elevation of the temperature to 40–46 °C, which induces the cancer cell death and enhances the effects of the radiotherapy and chemotherapy. In the present research, the realistic geometry of the human head layers and the tumor are modelled, geometrically, and then simulated similar to the real samples of MRI images with the size of 5990 mm 3 . The temperature distribution in the tumor and healthy tissues was obtained based on the solution of Penne’s bio-heat transfer equation utilizing the Finite Element scheme. Employing the accurate boundary conditions for the thermal simulation of the problem, two main layers of the human brain, namely, white matter (WM) and gray matter (GM), as well as the cerebrospinal fluid (CSF) and the skull, are considered in the thermal analysis. In order to examine the hyperthermia conditions, the effects of the different blood perfusion rates and tumor metabolism on the tumor temperature are analyzed. The results showed that by reducing the blood perfusion rate from 0.0016 to 0.0005(ml/(ml.s)), the temperature increased by nearly 0.2 ℃ at the center of the tumor implying that the variations of the blood perfusion rate in the tumor have not a significant influence on its temperature. Moreover, it was found that when the tumor metabolism increases five times (equal to 125 × 10 3 W/m 3 ) than its normal value (equal to 25,000 W/m 3 ), the temperature reaches to the range needed for ablation of the brain tumor (40–46 ℃). The results also indicated that the manipulation of the cancer tissues metabolic rate via thermal simulation could be efficiently employed to estimate the amount of heat needed for the thermal ablation of the tumor.